2005
DOI: 10.1002/chir.20123
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer separation of a powerful chiral auxiliary, 2-methoxy-2-(1-naphthyl)propionic acid by liquid chromatography using chiral anion exchanger-type stationary phases in polar-organic mode; investigation of molecular recognition aspects

Abstract: The enantiodiscriminating potential of the weak anion exchange-type quinine-based chiral stationary phases (CSPs) for direct enantiomer separation of racemic 2-methoxy-2-(1-naphthyl)propionic acid (selectand, SA) was studied. The influence of structure variations of the selector (SO) in the carbamate functional group and/or in the C6' position of quinoline moiety on retention and enantioselectivity was investigated. Systematic chromatographic studies were made to gain more insight into the overall chiral recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…When the methoxy group of quinine was replaced by a hydrogen (obtaining the corresponding cinchonidine derivative) in a previous chromatographic study, a stronger binding of the (R) enantiomer was observed (increase of k (R) ), being indicative for a better steric fit in the binding pocket also of the (R) enantiomer, which was accompanied by a lower enantioselectivity. 9 In contrast, when the methoxy group was replaced by more bulky alkoxy substituents (e.g., n-propoxy, isopropoxy, neopentoxy), the enantioselectivity was nearly lost and the lowered retention factors for both the (R) as well as the (S) enantiomers indicated that the perfect steric fit of the (S) enantiomer was lost due to steric overcrowding.…”
Section: X-ray Analysis Of 1:1 Complex Of Tbucqn With (S)-manp Acidmentioning
confidence: 94%
See 2 more Smart Citations
“…When the methoxy group of quinine was replaced by a hydrogen (obtaining the corresponding cinchonidine derivative) in a previous chromatographic study, a stronger binding of the (R) enantiomer was observed (increase of k (R) ), being indicative for a better steric fit in the binding pocket also of the (R) enantiomer, which was accompanied by a lower enantioselectivity. 9 In contrast, when the methoxy group was replaced by more bulky alkoxy substituents (e.g., n-propoxy, isopropoxy, neopentoxy), the enantioselectivity was nearly lost and the lowered retention factors for both the (R) as well as the (S) enantiomers indicated that the perfect steric fit of the (S) enantiomer was lost due to steric overcrowding.…”
Section: X-ray Analysis Of 1:1 Complex Of Tbucqn With (S)-manp Acidmentioning
confidence: 94%
“…14 For the more stable SOÁ(S)-SA complex, the signal of H 8 overlapped with H 6b at 3.60 ppm, making the assignment of the conformers more complicated. Among others, intramolecular NOEs were detected between proton pairs H 3V -H 7b , H 5V -H 9 , H 5V -H 8 /H 6b , H 9 The intramolecular NOE between H 101 and H 109 , and H 101 and H 102 of the SA allow to derive information on the preferential conformational binding state of the SA. From the former NOE, it can be concluded that the 1-naphthyl ring is oriented such that the proton H 109 and the methyl group C 101 are on the same side of the C 104 -C 108 axis, i.e., in syn orientation to each other (see Fig.…”
Section: Nmr Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…The opposite trend was found for pure enantioselective cation-exchanger-type CSPs, where the retention decreased, in the order TEA < DEA < EA < NH3, and base additive served as the counter-ions [50,57,84,85] .…”
Section: Figure 13 Effect Of Elution Strengths Of Co-and Counter-ionmentioning
confidence: 86%
“…They act as a competitor in the ion-exchange equilibrium. The addition of acid and base to the nonaqueous polar organic solvents greatly influences the solvation of both SO and SA, and the anions and cations of acid and base additives have great effects on the elution strength of the mobile phase, inversely acting as displacers at the cation-and anion-exchanger sites of the zwitterionic CSP, as summarized in Figure 13 [57,[84][85][86] . According to literature reports in single anion-exchange mode the base additives (co-ions)…”
Section: Effect Of the Nature Of Base And Acid Additivesmentioning
confidence: 99%